THE USE OF "CALLING A FRIEND" TECHNIQUES IN IMPROVING CHARACTER AND STUDENT'S LEARNING ACHIEVEMENT IN PANDEMIC TIMES - Ach. Andiriyanto; Nisfil Maghfiroh Meita (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
Some of the obstacles faced in learning during the pandemic are the learning that is applied does not activate students, students do not understand concepts, students are not disciplined in doing assignments, students only wait for material from the teacher. Selection of appropriate learning techniques is very important. The use of the calling a friend learning technique will make it easier for students to be more active in practicing speaking and listening. The purpose of the study is to provide an overview of the application of learning by using the calling a friend learning technique in character learning for students at SMPI Luqman Al Hakim Sumenep. Describes how to improve student learning achievement in listening and speaking by using the calling a friend learning technique at SMPI Luqman Al Hakim Sumenep. The research method is descriptive qualitative with the aim of getting an overview of the application of the Audio-Lingual Method, especially through a calling a friend learning technique. The research was carried out in Class VII SMP Luqman Al Hakim who applied the technique of calling a friend in learning English speaking and listening for 6 meetings. The research subjects were 2 English teachers and 40 seventh grade students. The results of the research using the calling a friend technique can improve the character of students, especially responsibility and discipline, even though the learning process is carried out online and is not directly monitored by the teacher. The percentage of learning achievement was 47.5% after the first cycle changed to 62.5%, in the second cycle it increased to 70% and reached 80% in the third cycle, meaning that student learning achievement has increased.